Room-Temperature Fiber-Coupled Single-Photon Source from CdTeSeS Core Quantum Dots - Surasak Chiangga (Photonics)
Single-photon sources with photon antibunching characteristics are essential for quantum information technologies. This paper investigates the potential of quaternary-alloy CdTeSeS colloidal core quantum dots (cQDs) as compact, room-temperature, and fiber-integrated single-photon sources. Single-photon emission from CdTeSeS cQDs was verified by measuring the second-order correlation function, <semantics>g<mfenced>2</mfenced><mfenced>τ</mfenced></semantics>, using a Hanbury-Brown and Twiss setup. A novel method to determine zero-time delay through afterpulsing analysis is presented. The results demonstrate strong photon antibunching with <semantics>g<mfenced>2</mfenced><mfenced>0</mfenced>=0.13</semantics>, confirming that the photoemission from the CdTeSeS cQDs function as a single-photon source. This work highlights the potential of CdTeSeS cQDs as reliable and efficient single-photon sources for practical use in fiber-based quantum information technologies.